Moldovan scientific conferences: Predatory or merely misguided? - Gheorghe Cuciureanu (European Science Editing)
Background: Predatory conferences vary greatly in their format, scale, and organization and adversely affect researchers from less developed countries the most. Although ways to identify such conferences continue to be refined, their organizers are often a step ahead and strive to be increasingly sophisticated. One effective way of detecting whether a given conference is predatory is to submit a nonsensical manuscript and monitor its fate.Objective: To examine the extent to which scientific conferences organized by institutions in Moldova match the established markers of predatory conferences.Methods: A manuscript authored by a fictitious individual was submitted to 16 scientific conferences. The manuscript included passages copied verbatim from other sources and introduced a fabricated and absurd indicator for evaluating science, namely the Timmy Index (named after the author’s dog). The conferences were subsequently matched against established markers for predatory conferences.Results: Of the 16 conferences, 14 accepted the manuscript; 9 issued a certificate of attendance; and 12 published the article in their proceedings, although none of the 16 charged any participation or publication fees.Conclusions: Pseudoscientific conferences are deeply embedded in the academic community of Moldova. The operational model employed by these conferences fosters a publication culture among local researchers that makes it acceptable to submit manuscripts to predatory journals and conferences, prioritizing rapid publishing for a fee and without proper peer review or an actual presentation at a conference.